2014
DOI: 10.1186/1753-2000-8-24
|View full text |Cite
|
Sign up to set email alerts
|

Adverse life events and delinquent behavior among Kenyan adolescents: a cross-sectional study on the protective role of parental monitoring, religiosity, and self-esteem

Abstract: BackgroundPast research provides strong evidence that adverse life events heighten the risk of delinquent behavior among adolescents. Urban informal (slum) settlements in sub-Saharan Africa are marked by extreme adversity. However, the prevalence and consequences of adverse life events as well as protective factors that can mitigate the effects of exposure to these events in slum settlements is largely understudied. We examine two research questions. First, are adverse life events experienced at the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 44 publications
2
40
0
1
Order By: Relevance
“…The study found that adolescents who were monitored reported fewer incidents of engagement in sexual behavior. Other studies with similar results include (Kabiru et al, 2014) who studied premarital sex among students. The studies mainly used samples of college students from developed countries and focused on a few parenting styles, on the other hand the study in Kenya by Wange'ri focused on parental monitoring.…”
Section: Review Of Related Literaturementioning
confidence: 70%
“…The study found that adolescents who were monitored reported fewer incidents of engagement in sexual behavior. Other studies with similar results include (Kabiru et al, 2014) who studied premarital sex among students. The studies mainly used samples of college students from developed countries and focused on a few parenting styles, on the other hand the study in Kenya by Wange'ri focused on parental monitoring.…”
Section: Review Of Related Literaturementioning
confidence: 70%
“…Studies ranged in sample size from 30 to 31 098 and were conducted in 13 SSA countries, with most conducted in Kenya, Ghana and South Africa. Some drew on large-scale national studies including: ‘Transition to Adulthood’ (TTA)47–49 and the ‘Cameroon Family and Health Surveys’ (CFHS) 50 51. Other studies reported findings from more than one SSA country 52–54.…”
Section: Resultsmentioning
confidence: 99%
“…The studies used various tools to measure child maladaptive behaviours including the Strengths and Difficulties Questionnaire83 85 86 and the delinquency sub-scale of the Child Behaviour Checklist-Youth Self Report 87. Results from the study of Kabiru et al 49 showed an association between the protective effect of parental monitoring and lower delinquency, but this was a poor-medium quality study 49. Four studies showed associations between harsh parenting (physical punishment/corporal punishment) and child externalising behaviours including ASB and aggression 84–87.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early negative experiences, including physical and sexual abuse, rejection and neglect from society, broken homes, impoverished financial status, domestic violence etc. are often faced by Children in Conflict with Law [1][2][3][4]. This installs in them frustration, feelings of insecurity along with a host of other disruptive emotional processes that eventually pave the way for impulsivity, anger outbursts, hostility and a tendency to violate the rights of others.…”
Section: Discussionmentioning
confidence: 99%